2013
DOI: 10.1007/s00464-013-3197-8
|View full text |Cite
|
Sign up to set email alerts
|

Submucosal tunneling endoscopic resection for small upper gastrointestinal subepithelial tumors originating from the muscularis propria layer

Abstract: Submucosal tunneling endoscopic resection appears to be a feasible, safe, and effective procedure for treatment of small (≤3 cm) upper GI SETs originating from the MP layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(68 citation statements)
references
References 18 publications
0
66
0
2
Order By: Relevance
“…Thus, submucosal injection of different solutions (such as glicerol or hyaluronic acid) a cushion beneath the lesion is created, separating the mucosa from the muscularis propia and enabling the tumor excision through a endoscopic submucosal dissection (ESD) (16,32), which safely allows enucleation of lesions that arise in the muscularis mucosae and the muscularis propia layer up to 3 cm. Endoscopic submucosal tunnel dissection (ESTD) has also been recently described, showing similar results and a lower risk of complications (27,28). We do not have enough experience in this kind of procedures, but we think they could be an available management alternative for experienced groups and small tumors, according to the published results (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, submucosal injection of different solutions (such as glicerol or hyaluronic acid) a cushion beneath the lesion is created, separating the mucosa from the muscularis propia and enabling the tumor excision through a endoscopic submucosal dissection (ESD) (16,32), which safely allows enucleation of lesions that arise in the muscularis mucosae and the muscularis propia layer up to 3 cm. Endoscopic submucosal tunnel dissection (ESTD) has also been recently described, showing similar results and a lower risk of complications (27,28). We do not have enough experience in this kind of procedures, but we think they could be an available management alternative for experienced groups and small tumors, according to the published results (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Currently, >20 studies have been published with outcome data based on >700 patients (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)22,29,30,(32)(33)(34)(35). In these studies, therapeutic success was recorded for >77% of patients and en bloc resection was achieved in >85% of patients, while irregularly shaped or larger tumors were risk factors in piecemeal resection (33).…”
Section: Efficacy Of Stermentioning
confidence: 99%
“…Gas-associated complications are the most common complications of STER and may occur in ≤66.7% of patients undergoing STER (10). Those patients who undergo full-thickness resection exhibit an increased rate of gas-associated complications, though the majority of these are clinically insignificant and may resolve spontaneously (7,10,12,13,29). Thoracic drainage is recommended for pneumothorax in patients with lung collapse >30% and symptoms that include dyspnea, and lung puncture is recommended for patients with pneumoperitoneum or emphysema and more apparent symptoms (29).…”
Section: Intraoperative Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted, however, that the authors selectively used endoscopic resection in patients with tumors exhibiting intraluminal growth, not in patients with extramural and mixed-type GISTs. Ye et al (5) have reported a higher risk of perforation in tumors located at…”
mentioning
confidence: 99%